2009
DOI: 10.1007/s10549-009-0323-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Gli1 correlates with the transition of breast cancer cells to estrogen-independent growth

Abstract: The failure of breast cancer treatment is largely due to the development of estrogen independence. Current data illustrate that Hedgehog (Hh) signaling may play an important role in breast cancer development. Here, we show that the expression of the Hh effector protein, Gli1 was significantly higher in estrogen-independent breast cancer cells than in estrogen-dependent cells. Our data showed for the first time that stable expression of Gli1 in ER positive breast cancer cell lines MCF-7 and T47D can induce estr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
1
12
2
Order By: Relevance
“…These findings indicate that, by regulating the continuous activation of breast CSCs, the Hh signaling pathway is involved, not only in progression, but also in invasion and metastasis. In addition, the expression of GLI1 was inversely correlated with ER, consistent with a previous study (32) that revealed that GlI1 expression was decreased in ER-positive breast cancer cell lines MCF-7 and T47D. These data indicate that GLI1 may attenuate the response to estrogenic stimulation by negatively regulating ER signaling, which may be the reason for TNBC patients exhibiting insensitivity to hormone therapy.…”
Section: Cd24supporting
confidence: 90%
“…These findings indicate that, by regulating the continuous activation of breast CSCs, the Hh signaling pathway is involved, not only in progression, but also in invasion and metastasis. In addition, the expression of GLI1 was inversely correlated with ER, consistent with a previous study (32) that revealed that GlI1 expression was decreased in ER-positive breast cancer cell lines MCF-7 and T47D. These data indicate that GLI1 may attenuate the response to estrogenic stimulation by negatively regulating ER signaling, which may be the reason for TNBC patients exhibiting insensitivity to hormone therapy.…”
Section: Cd24supporting
confidence: 90%
“…Although 60–70% of human breast cancers are ER-positive [27] and respond to anti-estrogen therapy, many of them will inevitably progress to the estrogen-independent stage and develop resistance to anti-estrogen therapy [14]. The existence of CSCs offers a simple explanation as to the presence of endocrine resistance in breast cancer [28-30].…”
Section: Discussionmentioning
confidence: 99%
“…Although abundant evidence has suggested that estrogen sustains the growth of breast cancer cells expressing functional estrogen receptors (ERs) [14], the role of estrogen in promoting breast CSCs remains controversial. Some researchers think that ER-positive cells contribute to the stem cell compartment directly stimulated by hormones [15,16], while others consider that estrogen may stimulate the expansion of a specific stem cell compartment in a paracrine manner [17-19].…”
Section: Introductionmentioning
confidence: 99%
“…GLI-mediated transcriptional activation results in the up-regulation of target genes including the transmembrane protein PTCH-1 and the transcription factor GLI-1 (Lum and Beachy 2004). It has been reported that over-expression of this pathway is highly associated with tumor development and progression in several types of human cancers including lung (Ruiz i Altaba et al 2002), human glioma (Kinzler et al 1981), biliary (Lauth and Toftgard 2007), and breast cancers (Zhao et al 2010). In addition, high expression of the Hedgehog target genes PTCH-1 and GLI-1 has been reported in chondrosarcoma cells (Tiet et al 2006).…”
Section: Discussionmentioning
confidence: 99%